2013
DOI: 10.1002/oti.1357
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study: Efficacy of Sensory Integration Therapy for Japanese Children with High‐Functioning Autism Spectrum Disorder

Abstract: This study's objective was to investigate the efficacy of sensory integration therapy (SIT) for children with high-functioning autism spectrum disorder (HFASD). The subjects were 20 HFASD children with IQs above 70 selected from previously collected data. Eight participated in individual SIT sessions, and 12 participated in group therapy (GT) including social skill training, communication training, kinetic activities, and child-parent play for 8-10 months. Changes in Total score and five Index scores on the Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 34 publications
(39 reference statements)
2
41
0
2
Order By: Relevance
“…Iwanaga et al [] is a nonrandomized study that compares outcomes data from children with ASD who received 9 months ASI intervention ( n = 8) to those who received 9 months of group therapy (social skills training, communication training, kinetic activities, and parent–child play; n = 12). The context and setting are a university‐affiliated medical center in Japan where a majority of sessions were held for both groups.…”
Section: Resultsmentioning
confidence: 99%
“…Iwanaga et al [] is a nonrandomized study that compares outcomes data from children with ASD who received 9 months ASI intervention ( n = 8) to those who received 9 months of group therapy (social skills training, communication training, kinetic activities, and parent–child play; n = 12). The context and setting are a university‐affiliated medical center in Japan where a majority of sessions were held for both groups.…”
Section: Resultsmentioning
confidence: 99%
“…For the three interventions of interest, CBT, occupational therapy and speech/language therapy, the PubMed search yields a total of 23,196 and 289 publications, respectively. Manuscripts were then selected based on the criteria outlined above.…”
Section: Resultsmentioning
confidence: 99%
“…In SI, patients are exposed to particular sensory stimuli and are taught to become adaptable to these environmental stimuli, while they are required to perform tasks 21 . Preliminary research has, in fact, shown that SI techniques, particularly those that follow Ayres Sensory Integration ® Fidelity Measure 22 , can have a more influential effect on improving sensory processing and regulation, sensorimotor skills and social-emotional function than fine motor therapy or group therapy 23 , and such strategies have been shown to be not only effective, but also safe and practical 24 , In fact, one of the first randomised controlled trials that examined the effects of SI showed a significant increase in the goal attainment scale (an individualised measure for progress), as well as a significant improvement in self-maintenance and social behaviour in subjects who received the OT intervention compared with those who did not 25 .OT can introduce tasks that teach proper sensorimotor performance. Imagine, for example, in order to teach an individual with ASD how to multitask, a therapist might have the child hang from a swing, trapeze or rope ladder 26 and have the child simultaneously attempt to complete a jigsaw puzzle-an exercise that would be intended to improve one's tolerance for a sensory overload.…”
Section: Occupational Therapymentioning
confidence: 99%
“…Own research conducted by Iwanaga et al (2014) in the group of 8 children with autism, Asperger`s disorder or pervasive developmental disorder who underwent SI therapy for eight months, showed significant http: //dx.doi.org/10.15405/epsbs.2017.10.73 Corresponding Author: Anna Studenska Selection and peer-review under responsibility of the Organizing Committee of the conference eISSN: 767 improvement in movement coordination and non-verbal cognitive skills. However, no improvement of verbal skills was registered.…”
Section: Introductionmentioning
confidence: 99%